Oribatid mites (Acari, Oribatida) from “Parco Naturale delle Alpi Marittime” (Piedmont, Italy) - Schatz, Heinrich; Fortini, Lorenzo; Fusco, Tommaso; Casale, Francesca; Jacomini, Carlo; Giulio, Andrea Di (Zootaxa, 2021)
Oribatid mites were investigated in six sites in the Alpi Marittime Natural Park (Prov. Cuneo, Piedmont, northern Italy) which is part of the NATURA 2000 network. The selected locations cover 4 forested (fir, ash, 2 beech forests) and 2 grassland sites (mountain meadow, xeric grassland). Altogether 173 described oribatid species belonging to 51 families were encountered, complemented by one undetermined species (Scheloribates (Topobates) cf. carpathicus), added together 174 species. Among them 11 species are new records for Italy. A comparison with other Italian alpine provinces shows high similarity of the oribatid species composition from the investigated sites with the provinces of Bolzano, Trento, Sondrio. A total of 37 species from the Marittime Alps has also been recorded in the southern part of the nearby Swiss canton Ticino. The majority of the species in the investigated sites are known as silvicolous; xerophilous species were mainly found in the xeric grassland site at lower altitude. High species similarities are observed between the forested sites, which also show high species numbers (up to 96 spp. found in the fir forest), lowest similarities are found between the open grassland sites and the forested sites, as well as between the grassland sites themselves.